Modeling and simulation on a water vapor high temperature heat pump system. (1st February 2019) - Wu, Di; Yan, Hongzhi; Hu, Bin; Wang, R.Z.
Abstract: In the face of more and more serious energy and environmental problems, energy conservation and environmental protection have attracted more attention all over the world. Combining the advantages of high temperature heat pump (HTHP) and natural refrigerant, water vapor HTHP system can effectively recover low-grade energy and is more green and environmental friendly. This paper presents a new water vapor HTHP system with 80–90 °C waste heat recovery and 120–130 °C hot water supply. The water vapor HTHP system model is established to investigate the system performance under different working conditions. Then, the experimental study of the HTHP system with water refrigerant is carried out to validate the simulation results. The simulation results present that when the evaporation temperature is under 83–87 °C and the condensation temperature among 120–128 °C, the compressor power ranges from 46.1 to 58.1 kW and system COP ranges from 3.64 to 4.87. The comparison between simulation and experimental results show good agreement with each other, which indicates that the model established in this paper has great reliability and accuracy for water vapor HTHP system. Highlights: A new HTHP system with water refrigerant was proposed to recover industry waste heat. A detailed model of the water vapor HTHP system was established to study the system performance. The water vapor HTHP shows good simulation and experimental performance. The average deviation of simulation and experimental results is about 5%.